Characterization of oviposition snail Pomacea flagellata (Say, 1827) under experimental conditions - de Jesús-Navarrete, Alberto (2016)
Pomacea flagellata is a conspicuous snail in tropical and subtropical areas of America; it has been consumed since pre-Hispanic times and now is considered overexploited. A four months cultivation experiment was realized to determine the substrate selection by females, size of clutches, water level for placing egg masses, number of offspring, and hatching time. We used three duplicate plastic vats that were filled with 100 L water, and three substrates were set inside: mangrove roots, reed and PVC pipes. A total of 57 eggs masses were recorder, 26 of them produced 5037 offspring. More eggs masses were set in the wall of vats (35), mangrove roots (18) PVC pipe 3 and reed only one. There were significant differences in the selection of the substrate, but not between the number of eggs masses and sex proportion. Average length of egg masses was 32.99 ± 10.92, width was 16.44 ± 5.1 and thickness 8.08 ± 3.87 mm. Average heights of the egg masses was 15.66 ± 3.42 cm, while hatching time was 13.30 ± 2.6 days, yielding between 94 to 301 offspring per spawning. Snails preferably used walls of vats and it is difficult to determine if they did not select a substrate. Water level in the vats was optimal and allowed to organisms place egg masses, offspring production is adequate and enough to start culturing programs to meat production, or to re stocking of natural environment.